(untitled) (Orfeu, 2024)
The present article intends to show an investigation (from an ongoing Master’s research project) on how much compositionality (from Paulo Costa Lima) could be connected with comprovisation, coming from the experience of musical creation for the cycle of pieces Abaeté, which is a project that intends to explore musically how much the region mentioned by the title of this conceptual work has been transformed in its ecology, experiencing violence in its urban growth. In order to bring an artistic conception of the invention of the world that is a reflection of the themes of the cycle of pieces and its "afrosurrealist comprovisation" in its aesthetic proposal, the group assembled to record was the Afluentes Ensemble. Within the scope of this investigation, a reflection on the provision in its definition begins, which has been obtained about the term in a few, but fundamental, academic works – especially from the notion of "notational perspective" of Sandeep Bhagwati and, from Julius Fujak, from the articulation of a transversal contemporary art in analogies with life situations. Then, the five vectors of compositionality are made known and defined as a method for perceiving the quality of what is composed: invention of worlds, criticality, inseparability between theory and practice, reciprocity and field of choices. The theories of comprovisattion, especially chosen, in their comprehensive description of open musical practices (as identified by Arthur Faraco) were those of Bhagwati and Fujak for a dialogue of ideas and a transversal convergence with Lima’s compositionality in each of its vectors for a synthesis of how the perception of a compropositionality (comprovisation and compositionality) would be realized). From selected excerpts from the pieces already composed for the Abaeté cycle (namely, Fragments of a Landscape, Dead Villages, Civilization or Barbarism, The New Legend of Abaeté, Topography in the Vicinity of the Dunes in Stella Maris and Contemplation on the Lagoons), we seek, finally, to highlight the strategies, practices and risks that would be imbricated in this perspective of musical creation from the context brought by the pieces of the cycle and for the cultural work carried out both when composing the material and what was done with the Afluentes Ensemble. Afrosurrealism was an aesthetic objective to be achieved as a result of the comprovisations, as well as the full definition of the proportionality from the study of the cycle of Abaeté pieces will continue to be investigated.